Outcome of early rehabilitation of patients with traumatic brain injury during COVID-19 pandemic in The Republic of Srpska, Bosnia and Herzegovina - Keleman, Nataša; Krasnik, Rastislava; Mikov, Aleksandra; Dragičević-Cvjetković, Dragana (Frontiers in Neurology, 2023)
Introduction The COVID-19 pandemic has placed a tremendous burden on the healthcare system. Patients with traumatic brain injury (TBI) have to get fast track treatment which is independent of environmental conditions. The aim of this study was to investigate epidemiological and clinical outcomes of early rehabilitation and compare it with the literature data during the non-COVID-19 period. Materials and methods A retrospective study included 174 patients with TBI, average 57 ± 19.08 years. They all underwent treatment in the University Clinical Center, Republic of Srpska, Bosnia and Herzegovina during the period January-December 2021. We have analyzed the epidemiological data and clinical course in 174 patients as well as the outcome of early rehabilitation in 107 patients. In clinical evaluation were used: Glasgow Coma Score (GCS), Functional Independence Measure (FIM) and Barthel Index on admission and at discharge, as well as Glasgow Outcome Scale (GOS) at discharge. ANOVA, SPANOVA, Student t-test and Pearson correlation coefficient were used in statistical analysis. The value (p < 0.05) was used for statistical significance. Results A total of 174 patients with TBI were included in this study. Most of the patients (n = 94) were older than 60, male (n = 125) and the most frequent cause of TBI was falling over (n = 88). About a half (n = 92) had a mild TBI, almost one third of the sample had moderate (n = 52), while only 30 patients had severe TBI. Total of 139 (80.3%) patients had the improved outcome, the worsening was registered in 2 (1.2%), while the fatal outcome was reported with 33 (18.5%) patients. When comparing the scores on admission and at discharge, the improvement of mean parameter values was reported for GCS (9.9 vs. 14.1), for Barthel Index (57.25 vs. 86.85), and for FIM (67.35 vs. 105.15), (p < 0.001). A complete recovery at discharge was found in 63.79%, a mild deficit in 8.62%, while serious deficit was found with 6.32%, and vegetative state with 2.29% patients. Conclusion The COVID-19 pandemic had a significant effect on the epidemiological data but not on the clinical outcome of patients with TBI. Early rehabilitation proved to be effective and to contribute to positive treatment outcome.